The Intersection of ‘Live’ and ‘Real-time’. - Hagan, Kerry L. (Organised Sound, 2016)
Real-time computer music is now common and ubiquitous, no longer a new or experimental practice. In its infancy, it helped to solve perceived issues with the fixity of tape pieces, a natural continuation in the practice of live electronics. However, real-time computer music did not have the same consequences as live electronic music. This situation engendered many discussions about the liveness of real-time computer music performances at the time. It is now 20 years past those first conversations, and it is important to revisit what is ‘live’ and how it applies to real-time musics. Additionally, in some ways, the language surrounding descriptions of fixed medium works, mixed works, live electronics and real-time computer music has evolved and, perhaps, even settled into conventions distinguishing musical approach and philosophies. This article first defines the language, not to proselytise, but rather to ground the argument. The conclusion asserts that liveness is a spectrum despite the fact that ‘live’ is often used categorically. Though one may have an intuitive understanding of what constitutes a ‘live’ event, this article explicitly articulates the most significantly contributive factors. The nature of real-time computer music is explored in relation to these factors of liveness. Using musical examples, this article shows that ‘real-time’ music does not guarantee a ‘live’ performance, contrary to what is typically held to be true. Instead, ‘real-time’ simply becomes a descriptor of compositional method, and any real-time work can exist along a broad range of the liveness spectrum.